Luminescence and scintillation response of YGd2Al2Ga3O12:Ce and LuGd2Al2Ga3O12:Ce scintillators. (July 2016) - Chewpraditkul, Warut; Pattanaboonmee, Nakarin; Chewpraditkul, Weerapong; Kamada, Kei; Yoshikawa, Akira; Nikl, Martin
Abstract: The luminescence and scintillation properties of YGd2 Al2 Ga3 O12 :Ce and LuGd2 Al2 Ga3 O12 :Ce single crystal scintillators were compared. The light yield (LY) and energy resolution were measured using R6231 photomultiplier. At 662 keV γ-rays, high LY value of 37, 900 ph/MeV and energy resolution of 7.0% obtained for YGd2 Al2 Ga3 O12 :Ce are slightly better than the values of 35, 400 ph/MeV and 7.6% obtained for LuGd2 Al2 Ga3 O12 :Ce. The ratio of LY values under excitation with α- and γ-rays (α/γ ratio) was also determined. The LY dependence on amplifier shaping time was measured in order to investigate the timing characteristics in the scintillation response. The estimated photofraction in pulse height spectrum of 662 keV γ-rays and the total mass attenuation coefficient at 662 keV γ-rays were also determined and compared with the theoretical ones calculated using the WinXCom program. Highlights: Luminescence of YGd2 Al2 Ga3 O12 :Ce and LuGd2 Al2 Ga3 O12 :Ce were studied. High LY value above 35, 000 ph/MeV was obtained for both crystals. Dependence of light yield on integrating time was examined. The LY ratio under α- and γ-excitation (α/γ ratio) was determined. Photofraction and attenuation coefficient at 662 keV were evaluated.